Spectrophotometric methods and magnifying endoscopy for differential diagnosis of colon lesions - А. А. Razgivina; А. М. Nechipai; А. V. Volova; S. М. Goryaev; А. А. Sokolov (Biomedical Photonics, 2013)
The review of recent development in diagnosis of premalignancy and early cancer in colon is represented. The results of several diagnostic methods which are supplemental for convenient colonoscopy, are described. Thus, NBI system (narrow spectrum endoscopy) and FICE combined with system for magnifying endoscopy significantly improve sensitivity and specifity of diagnostic method. However, the serious disadvantage is coloration of intestinal contents into different shades of red, impeding visualization of small structures and lesions. For detection of dysplasia of different degree in patients with colon polyps high levels of sensitivity and specifity were shown in the methods of magnifying and zoom-endoscopy (93.8% and 64.6%, respectively), confocal laser endomicroscopy (81% and 82%, perspectively), and optic coherent tomography (92% and 84%, respectively). The one of the most recent method – immunophotodiagnosis, showed high efficiency for detection of dysplasia and early cancer in patients with colon polyps: the sensitivity was 78.6%, specifity – 100%. Autofluorescence and fluorescence diagnostics with exogenous photosensitizers. The studies showed that autofluorescence diagnosis was valuable method for differential diagnosis of colon tumors (sensitivity was 85%, specifity – 81%).